Serum Proteome Profiling of Diabetic Patients Treated With DPP4 and SGLT2 Inhibitors Shows Improved Cognitive and Cardiovascular Functions - Hakim, Md Abdul; Sanni, Akeem; Osman, Shams T.; Hamdy, Noha A.; Purba, Waziha Tasnim; Bhuiyan, Md Mostofa Al Amin; Onigbinde, Sherifdeen; El‐Khordagui, Labiba K.; El‐Yazbi, Ahmed; Mechref, Yehia (Proteomics (Weinheim), 2025)
ABSTRACT Type 2 diabetes (T2D) is a complex metabolic disorder with rising global prevalence, leading to major complications such as cognitive decline, cardiovascular disease, and systemic inflammation. Although advances in T2D pharmacotherapy have shown promise in addressing these complications, the underlying protective mechanisms remain unclear, especially as they appear to be independent of glycemic control. In this study, we performed a comprehensive proteomic analysis using LC‐MS/MS to explore the molecular effects of newer antidiabetic drugs, specifically dipeptidyl peptidase 4 (DPP4) and sodium‐glucose cotransporter 2 (SGLT2) inhibitors (SGLT2is), when combined with metformin, the first‐line treatment for T2D. Serum samples from 76 individuals were analyzed, including 16 healthy subjects, 32 T2D patients on metformin monotherapy, and 28 T2D patients receiving combination therapy. We identified and quantified 505 low‐abundance proteins, followed by statistical analysis and ingenuity pathway analysis. Our findings revealed significant changes in key biological pathways related to synaptogenesis, insulin‐like growth factor transport, and neurovascular coupling signaling. These results were further validated using parallel reaction monitoring. Notably, pathways associated with cognitive function and cardiovascular health were adversely affected in T2D patients on metformin monotherapy but showed improvement with combination therapy. These results suggest that the combination of DPP4 and SGLT2is offers a therapeutic advantage, underscoring the importance of personalized treatment strategies in managing T2D complications. Summary: Type 2 diabetes (T2D) is a chronic metabolic disorder that contributes to the progression of cognitive impairment, cardiovascular diseases, and renal dysfunction. Cognitive decline in T2D patients can also increase the risk of developing neurological conditions like Alzheimer's disease. Recently developed antidiabetic drugs have shown promising cardiovascular and renal health effects, such as dipeptidyl peptidase 4 (DPP4) inhibitors and sodium‐glucose cotransporter 2 (SGLT2) inhibitors (SGLT2is). However, the precise mechanisms by which these drugs influence biological pathways related to cognitive function and central nervous system (CNS) development remain unclear. In this study, we explored the impact of these newer antidiabetic drugs in combination with metformin, compared to metformin monotherapy and healthy controls, by investigating differentially expressed proteins and their role in cognitive processes. Our findings reveal that DPP4 and SGLT2is activate key biological pathways—such as synaptogenesis, insulin‐like growth factor regulation, and neurovascular coupling—that are either suppressed or not enriched in the metformin‐only group. These pathways are critical for maintaining and regulating CNS function and cognitive health.